NITROGEN AND PHOSPHOR AVAILABILITY ANALYSIS AND MODELING- IN NILE TILAPIA (Oreochromis niloticus L.) AND KALE (Brassica oleracea var. Acephala) CULTIVATION USING APPLICATION OF RAS (RECIRCULATING AQUCULTURE SYSTEM) TECHNOLOGY - Dhiaulhaq Gilang Indryan (Nim : 11414003), Aufa
Recirculating aquaculture system (RAS) are modern aquaculture method that can save water usage up to 99,6% compared to conventional method. Integration of fish and plant cultivation or also known as aquaponic can be made using this method because this system have the capability to provide nutrition for plants to use. This study aims to measure application of RAS technology performance in integrated cultivation of nile tilapia (Oreochromis niloticus) and kale (Brassica oleracea var Acephala). Performance observed were nitrogen and phosphor availability in each of system components, and its mathematical equation which describe the nutrients availability during the study. Results shows that average level of ammonium, nitrthite, nitrate, and orthophosphate during this study are 1,28; 2,71; 11,98; and 8,02 ppm respectively. The availability of ammonium, nitrite, nitrate, and orthophosphate during this study can be described using 6th order of polynomial regression, with R2 value of 0,9994; 0,9722; 0,9918; and 0,9309 respectively.